Issues and challenges of accessibility for senior tourism (Estoril/Portugal) - Sarmento, Eduardo Moraes; Brás, Catarina; de Oliveira, Carla Vargas (Revista Lusófona de Economia e Gestão das Organizações, 2016)
The behavior of tourism activity worldwide, particularly with regard to some fringepopulation with some degree of disability, came to redefine the opportunities for developmentof new tourist offers and simultaneously has imposed new challenges. Thisarticle analyzed the topic of accessibility regarding senior population that goes to theEstoril line and is hosted in five star hotels.We intend in an early stage to realize the scope of this phenomenon and assess on thelevel of care offered and in a second phase to try to conclude whether this region canbe seen as a fully accessible destination.We applied several interviews complemented some questionnaires to those responsiblefor ten 5 star hotels situated in Estoril coast, over a period of two months in 2013.It was verified that tourism in this region is only partially accessible as it does notcover all types of disabilities and because the available resources available were notinterconnected in accessible routes.